Pengaruh Keikutsertaan Siswa dalam Kajian Studi Islam terhadap Hasil Belajar Fiqih di MAN 3 Inhil - Jumadi; Salmiwati (YASIN, 2026)
Kajian Studi Islam as a religious development program in madrasahs has received attention in various studies, but research specifically analyzing the effect of students’ participation in the program on Fiqh learning outcomes at Madrasah Aliyah remains limited. This study aimed to analyze the effect of Kajian Studi Islam on students’ Fiqh learning outcomes at MAN 3 Indragiri Hilir. The study employed a quantitative approach with an ex post facto design and correlational analysis involving 54 eleventh-grade students selected through purposive sampling. Data were collected using a questionnaire that had been tested for validity and reliability and were subsequently analyzed with the assistance of IBM SPSS Statistics version 22 through descriptive analysis, normality testing, linearity testing, and simple linear regression. The results showed that the instrument met the validity and reliability criteria, with a Cronbach’s alpha value of 0.741. Hypothesis testing showed that Kajian Studi Islam had a positive and significant effect on Fiqh learning outcomes, as indicated by a calculated t-value of 2.249, which was greater than the critical t-value of 2.042. These findings confirm that the implementation of Kajian Studi Islam plays a role in supporting improvements in students’ Fiqh learning outcomes. Theoretically, this study extends the literature on Islamic Religious Education concerning the relationship between religious development programs and academic achievement, while practically, the results can serve as a basis for madrasahs to optimize Kajian Studi Islam as a supporting program for Fiqh learning.